THE USE OF A CORPUS TOOL ANTCONC FOR TEACHING GERMAN GRAMMAR - Pujiastuti, Suci (Universitas Negeri Surabaya, 2025)
The aim of this research is to develop a corpus method specifically for learning and teaching German for B1 level grammar courses for German students. This research uses a corpus-based development method by Scherer [9] with several phases, namely: collecting corpus data, inputting data in the corpus tool, reading data in the corpus tool, validation of data and using the corpus for teaching of German grammar (Grammatik). Grammatik is the knowledge of grammar or the rules used in writing and speaking German. This field has many rules and German students, especially in the German Language Education Study Program, Faculty of Languages ​​and Arts, Universitas Negeri Medan, often face difficulties in the process of understanding grammar, so a method is needed, namely the Corpus method, to study German grammar.